AuPt bimetallic loaded defect state g-C3N4 enhances photocatalytic H2 evolution: exploring synergistic effects and charge transfer mechanisms - Zhao, Yahao (2024)
AuPt alloy nanoparticles (NPs) were prepared using a simple photodeposition method to modify defective state g-C3N4 nanosheets (HCN) which contained N vacancies, B doping, and –C[tbnd]N groups. The visible diffuse reflectance spectra (DRS) indicate that AuPt/HCN exhibits high light absorption capability. The photoluminescence spectrum (PL) and steady-state surface photovoltage (SPV) indicate that AuPt/HCN possesses a high rate of photogenerated charge separation and a high efficiency of photogenerated electron transfer. The electrochemical tests indicate that AuPt/HCN exhibits lower electrochemical impedance. AuPt/HCN (1.0 wt%) exhibits outstanding photocatalytic hydrogen evolution efficiency, producing hydrogen at a rate of 2095 μmol·g−1·h−1 under visible light, which is 2.10 times and 1.55 times higher than that of monometallic Au/HCN (1.0 wt%) (997 μmol·g−1·h−1) and Pt/HCN (1.0 wt%) (1349 μmol·g−1·h−1), respectively. The bimetallic synergistic effect of AuPt alloy NPs co-catalysts enhances the photocatalytic hydrogen evolution activity of AuPt/HCN composite photocatalysts.